'She thinks her toys don't understand Romanian': family engagement with children's learning during the transition to school. Issue 2 (4th March 2018) - Rogers, Susanne
ABSTRACT: This article reports on the perspectives of mothers and educators in relation to the engagement of mothers in their children's learning as children living in complex circumstances made the transition to school. For the purposes of this study, family engagement related to engaging with children's learning, which may not necessarily equate to engagement with the school. The study investigated ways in which mothers engaged with their children's learning as they made the transition to school and the perspective of educators in relation to this engagement. It was conducted in four communities characterised by complexity and diversity, in the metropolitan area of the capital city in a southern Australian state. Participating mothers and educators were interviewed individually. Data were analysed using a constructivist grounded theory approach to enable a focus on the lived experiences of individuals in the contexts of their circumstances. The resultant analysis, in relation to the engagement of mothers with their children's learning, identified differences in the perspectives of mothers and educators. Mothers reported a range of ways in which they engaged with their children's learning, the types of learning they valued and their role in that learning. Educators, generally, viewed family members as being deficient in the knowledge and skills to support their children's learning, requiring specific instruction from educators.